2020
DOI: 10.1155/2020/5917382
|View full text |Cite
|
Sign up to set email alerts
|

Health‐Related Quality of Life in Patients with Lung Cancer Applying Integrative Oncology Concepts in a Certified Cancer Centre

Abstract: Background. Pretreatment health-related quality of life (HRQOL) is associated with survival outcome in lung cancer patients. There is a lack of systematic research on pretreatment HRQOL in lung cancer patients who receive integrative oncology (IO). We evaluated patient-reported outcomes in these patients at time of diagnosis at a certified oncology and lung cancer centre. Methods. The present analysis is a prospective real-world data study. Clinical and demographic data were obtained from the accredited Networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 39 publications
(44 reference statements)
2
4
0
Order By: Relevance
“…Completed EORTC QLQ-C30 questionnaires were evaluated and analyzed for the entire study cohort at T0 and T1. All EORTC QLQ-C30 scores at T0 were within the range of formerly published EORTC QLQ-C30 reference values for LC patients [ 25 ] and similar as published previously [ 14 ]. In Table 3 , the mean values for T0 and T1 for all EORTC QLQ-C30 scales and the means and IQR of the longitudinal changes for all scales were determined.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Completed EORTC QLQ-C30 questionnaires were evaluated and analyzed for the entire study cohort at T0 and T1. All EORTC QLQ-C30 scores at T0 were within the range of formerly published EORTC QLQ-C30 reference values for LC patients [ 25 ] and similar as published previously [ 14 ]. In Table 3 , the mean values for T0 and T1 for all EORTC QLQ-C30 scales and the means and IQR of the longitudinal changes for all scales were determined.…”
Section: Resultssupporting
confidence: 88%
“…In a previous real-world data (RWD) study we found, that the risk of death was reduced in patients with tumor stage IV NSCLC treated with a combination of chemotherapy and VA, compared to chemotherapy alone [ 11 ]. Only few publications so far have addressed self-reported QoL in LC patients [ 2 , 3 , 12 14 ]. In a further RWD study, our group has shown that LC patients, age-dependently or tumor stage-dependently report increased pain, low mood and financial difficulties at diagnosis before treatment [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings corroborate those of previous studies conducted in the USA and Europe showing that baseline HRQoL can serve as a prognostic indicator 28 29. These observations imply that patients with low baseline HRQoL may be more fragile and vulnerable, and may be at higher risks for financial difficulties, and were thus less likely to receive adequate antitumour treatment 17 30. Nevertheless, we could not establish associations between baseline HRQoL and response to treatment.…”
Section: Discussionsupporting
confidence: 82%
“…In the hospice phase, it is crucial to clarify the patient's individual needs because not all patients die within a few weeks. Common symptoms, fatigue, and pain affect patients' functional capacity [17][18][19][20] and the patients often suffer from psychological distress, death anxiety, the inability to cope and the fear of their condition worsening in the near future [21][22][23][24]. Cancer fatigue may be persistent and affect patient's social relationships and quality of life.…”
Section: Introductionmentioning
confidence: 99%